Tradisi Ruwat Bumi di Tengah Perubahan Sosial: Konflik Budaya Pengaruh Nilai dan Norma di Desa Guci Kecamatan Bojong Kabupaten Tegal - Putri Uminatul Awalliyah; Indah Mustafidah; Nurul Mubin (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2024)
The tradition of Ruwat Bumi in Gusi Village, Bojong District, Tegal Regency is a manifestation of local wisdom that has existed for a long time. This tradition is carried out as an expression of gratitude to God. blessings of the earth and pray for the safety and blessings of the village. However, in the midst of rapid changes in society, this tradition is increasingly popular because of the difference in values and norms between groups that support the preservation of the tradition and those who consider this practice not to contradict the teachings of Islam in various challenges, including conflicts of interest. This research was conducted with the aim of identifying the factors that cause cultural conflicts, analyzing the impact of social changes on the sustainability of the Ruwat Bumi tradition, and examining the role of values and norms in maintaining or rejecting these traditions. In this study, a qualitative approach method was used that involved observation techniques, interviews, and literature reviews. The results of the study show that cultural conflicts occur due to differences in understanding of religion, modernity, and cultural preservation. Nevertheless, the Ruwat Bumi tradition still has important values in maintaining social solidarity and cultural identity of the people of Guci Village. This research is expected to provide a deeper understanding of cultural dynamics in the face of social change and the importance of intercultural dialogue in maintaining community harmony.